Pelatihan Kepemimpinan Sebagai Bentuk Peningkatan Kinerja Di PT. Fumira - Linda Purnamasari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
unning a company is not easy without a leader. It is not easy to find a leader and also make him able to run a company so that the company can generate a lot of profit and can last a long time. Once there are leaders, they must continue to be trained so that their quality is maintained. To maintain them, the existing leaders must be given training. Inside PT. Fumira which consists of many units, it takes many leaders to manage the company in order to survive. PT. Fumira needed a reliable leader. For this reason, skilled leadership is required in carrying out internal and external tasks. It is not easy to run, it takes a lot of skills, one of which is leadership training. By involving all the leaders in each must always be added to the knowledge of leadership. Likewise for the leadership at P.T Fumira. For this reason, the community service team from Esa Unggul University supported by lecturers who are reliable in their fields provide leadership knowledge to leaders at PT. Fumira